Difficult contextos and turbulento stories as triggers for innovation - Altopiedi, Mariana; López Jiménez, Luis Carlos (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This article debates a frequently sustained idea about educational innovation which is that it needs a very favorable environment to be initiated and, especially, to get sustainable. In contrast, our study –which is part of a wider research- puts in evidence that a difficult context and a turbulent history may often work as an excellent lever of change processes. That is the case of the schools analyzed in this paper.